Environmental costs and their impact on the net present value of a hydro-electric project in Kerala, India - V. SANTHAKUMAR and ACHIN CHAKRABORTY (Environment and Development Economics 8: 311-330 2003, 2003)
This paper presents the operational procedures involved in incorporating the environmental costs in the cost-benefit analysis of a hydro-electric project. The proposed project, if implemented, would result in the loss of 2,800 hectares of tropical forests and dislocation of two settlements of about 200 families who are currently dependent on the forests for their livelihood. The forests are mainly used for extracting reed a material used both by traditional artisans and the paper-pulp industry. The potential environmental costs and benefits of the project are identified and approximate estimates of some of these costs are made for items such as carbon sequestration, bio-diversity, and so on, based on similar estimates made elsewhere. These estimated environmental costs are incorporated into the analysis, and the hypothetical estimate of the non-use value,which would make the project's net benefit zero, is estimated under different discount rates. The analysis brings into sharp focus some crucial factors that have a direct bearing on the social trade-off involved in the project choice.